2012
DOI: 10.1186/1687-3963-2012-9
|View full text |Cite
|
Sign up to set email alerts
|

A space-time coding approach for RFID MIMO systems

Abstract: This paper discusses the space-time coding (STC) problem for RFID MIMO systems. First, a mathematical model for this kind of system is developed from the viewpoint of signal processing, which makes it easy to design the STC schemes. Then two STC schemes, namely Scheme I and Scheme II, are proposed. Simulation results illustrate that the proposed approaches can greatly improve the symbol-error rate (SER) or bit-error rate (BER) performance of RFID systems, compared to the non space-time encoded RFID system. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 12 publications
(24 reference statements)
2
18
0
Order By: Relevance
“…The power of the interfering signal that reader x receives from reader y is calculated in the same way as Equation 9:…”
Section: Single-channel Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The power of the interfering signal that reader x receives from reader y is calculated in the same way as Equation 9:…”
Section: Single-channel Modelmentioning
confidence: 99%
“…RFID is used for many applications, such as traceability [2], item removal detection [3], anti-counterfeit [4] and positioning [5], and for the establishment of smart environments, such as smart retailers [6], smart hospitals [7], and smart universities [8]. Although the need of covering large areas has been partially satisfied by using MIMO RFID readers [9], the majority of the RFID applications, especially the largest, require a dense reader deployment, where RFID readers operate in close proximity. Consequently, UHF RFID systems are easy to suffer from the interference generated during simultaneous interrogation activities [10].…”
Section: Introductionmentioning
confidence: 99%
“…To mitigate such fading, the use of multiple antennas at the reader or tag has been investigated by a number of researchers [3]- [6]. In [3], it was shown that pinhole diversity is available in a rich scattering environment caused by modulating backscatter with multiple tag antennas, and can yield a significant reduction in the power required to maintain a certain bit error rate (BER).…”
Section: Introductionmentioning
confidence: 99%
“…In [5], the authors showed how transmit diversity and spatial multiplexing can be applied to a multiple-antenna RFID system to dramatically increase the interrogation range and data rates. In [6], the space-time coding problem for multiple-antenna RFID systems was discussed, and coherent space-time coding schemes capable of achieving spatial diversity were proposed. It is noteworthy that [4]- [6] assume perfect knowledge of the forward and backward channels at either the transmitter side or the receiver side of the reader.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation